Efficacy of Fixing Chest Tube to Chest Wall from Both Sides versus Single Side Fixation with Silk One Breaded Suture - Raza, Ahmed; Yasser Saeed; Majeed, Farhan Ahmed; Waqas, Ahmed; Ashraf, Imran; Masood, Salahudin (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the efficacy of fixing chest tube to chest wall from both sides versus single side fixation with silk one suture.Study Design: Comparative cross sectional study.Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Mar 2021 to Jan 2022.Methodology: Two hundered Patients undergoing chest intubation at CMH Kharian and referred from peripheral hospitals were considered in the study and divided into two groups. In our setup (Group-A), chest tubes were fixed with a chest wall with silk breaded sutures from both sides, compared to patients referred from peripheral hospitals (Group-B), who had chest tubes fixed to the chest on a single side. They were analyzed for system leakage at the chest wall, to and fro movements of the chest tube and accidental dislodgement.Results: Unilateral chest intubation was done in 193(96.5%). Right sided intubations were 112(56%) and 81(40.5%) were left sided. Most chest intubations done were either blunt or penetrating thoracic trauma 52(26%), early empyema thoracis 50(25%), primary pneumothorax 30(15%), indeterminate pleural effusion 28(14%), secondary pneumothorax 24(12%) and malignant pleural effusion 16(08%). System leakage was 2(02%) in group A to 13(13%).No chest tube was moved to and fro in Group-A and 12(12%) in Group-B. In Group-A, accidental dislodgement was 3(03%), and 6(06%) patients had such complication in Group-B.Conclusion: Chest tube fixation with chest wall with silk one breaded suture gives better support to the chest tube from all sides and minimizes the chances of system leakage, to-and-fro moveme